HEALTH VARIABLES AND PROFESSIONAL PRACTICE PROFILE OF BALLROOM DANCE TEACHERS IN BRAZIL - Allana Alencar; Amanda Rodrigues Alves de Almeida; Gelcemar Oliveira Farias; Juarez Vieira do Nascimento; Adriana Coutinho de Azevedo Guimarães (Journal of Physical Education)
ABSTRACT The objective was to investigate fatigue, quality of life (QoL) and professional profile of ballroom dance teachers in Brazil compared by gender. A total of 272 professionals from the five regions of Brazil were evaluated using a self-administered questionnaire divided into professional profile, QoL and fatigue. It was observed that women showed better results compared to men in terms of education and BMI. The general QoL of both sexes showed regular scores, with higher values for the social relations domain and lower values for the physical domain. The data reflect the search for information on the profile of the ballroom dance teachers and health factors related to their professional practice profile, with possible distinctions between the sexes and highlight the importance of awareness for the maintenance of the health of dance professionals.